Individual and time effects in nonlinear panel models with large N, T - Iván Fernández-Val; Martin Weidner (Centre for Microdata Methods and Practice (cemmap), 2013)
Fixed effects estimators of nonlinear panel data models can be severely biased because of the well-known incidental parameter problem. We develop analytical and jackknife bias corrections for nonlinear models with both individual and time effects. Under asymptotic sequences where the time-dimension (T) grows with the cross-sectional dimension (N), the time effects introduce additional incidental parameter bias. As the existing bias corrections apply to models with only individual effects, we derive the appropriate corrections for the case when both effects are present. The basis for the corrections are general asymptotic expansions of fixed effects estimators with incidental parameters in multiple dimensions. We apply the expansions to M-estimators with concave objective functions in parameters for panel models with additive individual and time effects. These estimators cover fixed effects estimators of the most popular limited dependent variable models such as logit, probit, ordered probit, Tobit and Poisson models. Our analysis therefore extends the use of large-T bias adjustments to an important class of models. We also develop bias corrections for functions of the data, parameters and individual and time effects including average partial effects. In this case, the incidental parameter bias can be asymptotically of second order, but the corrections still improve finite-sample properties.
Keywords: C13; C23; 330; Panel data; asymptotic bias correction; fixed effects